Kajian Peningkatan Produksi pada Kegiatan Penambangan Pasir di PT Fajar Parahiyanan Desa Kandangmukti, Kecamatan Leles, Kabupaten Garut, Provinsi Jawa Barat - Ibnu Sucipto; Dudi Nasrudin Usman; Sri Widayati (UNISBA Press, 2022)
Abstract. The development of the west java in the last 10 years has continued to increase, especially physical development. The increase in development activities requires mining companies to continue increase their porduction, to meet the needs of contstruction materials in the current and future development proceess.In order to meet the need for raw materials for construction activities, this research is designed in such a way that it can increase production in mining activities at PT Fajar Parahiyangan, taking into account the factors that influence production activities so as to maximize production activities. The actual production at the mining site for the Sumitomo SH-210 digging equipment is 12,717.063 tons/month, while for the Mitsubishi Fuso HD-125 conveying equipment it is 12,689.534 tons/month. After optimizing the loading of transportation equipment, the production of digging-loading equipment is 13.390.929 tons/month and the production of transportation equipment is 13.617.064 tons/month. As a result of improving work efficiency, the production of digging-loading equipment is 18,318,471 tons/month and for transportation equipment of 18,302,460 tons/month. Abstrak. Pembangunan wilayah Jawa Barat dalam kurun waktu 10 tahun terakhir terus meningkat, khususnya pembangunan secara fisik. Meningkatnya kegiatan pembangunan tersebut menuntut perusahaan-perusahaan tambang terus meningkatkan produksinya, untuk memenuhi kebutuhan material konstruksi pada proses pembangunan saat ini dan masa yang akan datang. Dalam rangka memenuhi kebutuhan akan bahan baku kegiatan konstruksi tersebut, maka penelitian ini dirancang sedemikian rupa sehingga dapat meningkatkan produksi pada kegiatan penambangan di PT Fajar Parahiyangan, dengan memperhatikan faktor-faktor yang berpengaruh dalam kegiatan produksi sehingga dapat memaksimalkan kegiatan produksi. Produksi aktual di lokasi penambangan untuk alat gali-muat Sumitomo SH-210 adalah sebesar12.717,063 ton/bulan, sedangkan untuk alat angkut Mitsubishi Fuso HD-125 adalah sebesar 12.689,534 ton/bulan. Setelah dilakukan optimalisasi pada pengisian alat angkut didapatkan produksi alat gali-muat sebesar 13.390,929 ton/bulan dan produksi alat angkut sebesar 13.617,064 ton/bulan. Untuk hasil dari perbaikan efisiensi kerja didapatkan produksi alat gali-muat sebesar 18.318,471 ton/bulan dan untuk alat angkut sebesar 18.302,460 ton/bulan.